Effect of sowing dates and irrigation schedules on performance of Indian mustard (Brassica juncea L.) and water use efficiency - SINGH, PANKAJ KUMAR; SINGH, A. K. (Journal of Soil and Water Conservation, 2020)
A field experiment was conducted during the rabi seasons of 2010-11and 2011-12 to assess the effect of different dates of sowing and irrigation schedules on Indian mustard (Brassica juncea L.). The experiment was conducted with split plot design and replicated three times. Treatments consisted of three dates of sowing viz., D1 (30th October), D2 (14th November) and D3 (29th November) allotted to main-plot and four irrigation schedules viz., I1 (Irrigation at 0.5 IW/CPE ratio), I2 (Irrigation at 0.7 IW/CPE ratio), I3 (One irrigation at pre-bloom stage) and I4 (Two irrigation at pre-bloom stage + pod filling stage) assigned to sub-plots. Results revealed that all the yield attributes increased significantly under 30th October sowing. Number of siliquae plant-1, number of seeds siliqua-1, length of siliqua (cm) and seed and stover yields were significantly higher with irrigation at 0.7 IW/ CPE ratio. Interaction between dates of sowing and irrigation schedules was significant on mustard seed yield. The highest seed yield (16.4 q ha-1) was recorded with 0.7 IW/CPE ratio sown on 30th October. The highest net return and B:C ratio were recorded under 30th October sowing and irrigation at 0.7 IW/CPE ratio. The highest water-use efficiency (WUE) (146.5 kg ha-1 cm-1) was recorded under 30th October sowing. Among irrigation scheduling, one irrigation at pre-bloom stage resulted in highest WUE (148.9 kg ha-1 cm-1). 30th October sowing with irrigation at 0.7 IW/CPE ratio proved most remunerative and economically feasible for cultivation of Indian mustard under the agroclimatic conditions of eastern Uttar Pradesh.